1 - Soft Power Diplomacy: Analytical and Conceptual Contextualization of Cuba’s Peregrination in Africa - Suping, Kekgaoditse; Adar, Korwa Gombe (Africa Development, 2024)
For decades, and despite sanctions and turbulent relations with major international actors since the 1960s, Cuba has managed to assert itself in the international system. A small island with very limited natural resources, Cuba leveraged its international affairs on its provision of healthcare. This article investigates the role and impact of Cuban medical assistance in Africa. It proceeds from the premise that soft power has useful explanatory value in understanding the Cuba–Africa diplomatic intercourse. The article argues that despite its political ideology and limited political freedoms, Cuba established itself as a model and prominent player in the unique and consistent provision of healthcare and humanitarian assistance to the African continent, and in the development of Africa’s healthcare systems, for more than sixty years. It has also offered community-based healthcare training, which most African countries consider to be more relevant and cost-effective than hospital-based training. Furthermore, the Cuban training gave African medical students a shift in perspective and orientation to focus on public service, not profit-making.